The communication and language profile of an adolescent girl following surgery for a benign frontal-parietal tumor - Giannakou, Eleni (My University, 2022)
Background: A neoplastic and abnormal growth of cells in the brain is defined as brain tumor/lesion/neoplasia. Damage to the frontal and parietal lobes can cause many dysfunctions, hence there is a need for Speech and Language Therapy (SLT) in the presence of cognitive communication deficits. Aim: To evaluate communication and language functions in an adolescent girl following surgery for a Benign Frontal-Parietal Tumor (BFPT). Method: A single case-study design was used. Assessment of language functions included speech and reading samples, administration of speech and language diagnostic tools and the completion of relevant questionnaires by the participant and her parents. Results: The results revealed that the participant had intact content and use of language, speech and reading flow and fluency and theory of mind. Deficits were identified in executive functions and production of metaphors. Also, after the surgery C.C. felt more mental fatigue/tiredness and some changes in her personality were noted that impacted her social life and emotions. Conclusions: BFPT affected communication and language domains as well as the participant’s personality and emotions. It is argued that some of the functions were intact due to brain plasticity and SLT. Nevertheless, damage to the area caused difficulties mainly in cognition, personality and mental fatigue. Overall, SLT service provision for individual with FPBT during the first months after surgery benefits all aspects of life
Keywords: Benign frontal-parietal tumor; Adolescent benign tumor survivors; Language; Cognition